Serological evidence of high leptospira exposure among indigenous people (Orang Asli) in peninsular Malaysia using a recombinant antigen-based ELISA - Loong, Shih Keng; Khor, Chee Sieng; Chen, Hua Wei; Chao, Chien Chung; Ling, I.S.C.; Abdul Rahim, N.F.; Hassan, Hamimah; Nellis, S.; Ching, Wei Mei; AbuBakar, Sazaly (Malaysian Society of Parasitology and Tropical Medicine, 2018)
The lifestyles of the indigenous people (Orang Asli) of Peninsular Malaysia who traditionally live close to the forest, put them at higher risk of exposure to zoonotic diseases. Leptospirosis has recently emerged as one of the most important diseases of public health concern. Here, we aimed to obtain a baseline data on the level of Leptospira exposure among the 107 Orang Asli volunteers using a recombinant antigen-based ELISA, previously shown to have sensitivity of ~90.0% in comparison to the microscopic agglutination test (MAT). Among the Orang Asli volunteers in this study, 60.7% had IgM against Leptospira and 57.9% were anti-Leptospira IgG positive. Of these seropositive individuals, 29.9% had both anti-Leptospira IgM and IgG antibodies. Age was found to be a significant predictor for exposure to Leptospira (P < 0.05) with the younger Orang Asli population more likely to be tested positive for anti-Leptospira IgM. The finding of high Leptospira exposure among the Orang Asli volunteers could be due to their socio-economic practices and dependency on the forest for their livelihood. The rapid and sensitive recombinant antigen-based ELISA used in the study, could possibly complement MAT for the epidemiological surveillance of leptospirosis, especially among the underserved populations.